2017
DOI: 10.3390/agronomy7010013
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Positive Synergistic Effect of Biochar and Compost Soil Amendments on Plant Growth and Physiological Performance?

Abstract: Abstract:The combination of biochar (BC) with compost has been suggested to be a promising strategy to promote plant growth and performance, but although "synergistic" effects have been stated to occur, full-factorial experiments are few, and explicit tests for synergism are lacking. We tested the hypothesis that a combination of BC and spent mushroom substrate (SMS) has a positive synergistic effect on plant growth and physiological performance in a nutrient-limited growing media. A greenhouse experiment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 79 publications
(123 reference statements)
4
27
2
Order By: Relevance
“…Recent work demonstrated substantially increased flower and fruit production in A. theophrasti , and early onset of flowering up to two weeks when a high‐temperature mixed‐wood biochar was applied to a non‐soil medium (Seehausen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work demonstrated substantially increased flower and fruit production in A. theophrasti , and early onset of flowering up to two weeks when a high‐temperature mixed‐wood biochar was applied to a non‐soil medium (Seehausen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have pointed to a synergistic effect of biochar with compost that can mediate the soil microbial process, affecting soil nutrient cycles [21], promoting C stabilization though the formation of organo-mineral complexes [22], improving plant growth by nitrate-capture in co-composted biochar [23] or forming a coating on the outer and inner surfaces of biochar particles that adds hydrophilicity, redox-active moieties, and additional mesoporosity, which enhances biochar water interactions and thus increases nutrient retention [24]. However, this effect has not been corroborated, as other authors have found neutral or antagonistic interactive effects on several plant traits from blends of biochar and compost [25]. Either way, we hypothesize that the utilization of biochar and compost blends represents a valid strategy to enhance nutrient recovery from waste and increase water content, nutrient use efficiency, C storage, and microbial activity in soils [26].…”
Section: Introductionmentioning
confidence: 99%
“…Organic fertilizer may form a coating inside and outside the biochar particle and increase hydrophilicity, thus raising the nutrient retention [29]. However, the antagonistic or neutral effect of manure and biochar interaction has been reported in studies [30][31][32].…”
Section: Introductionmentioning
confidence: 99%